Pardosa acorensis - Borges, Paulo A. V. (2021)
JUSTIFICATION: Pardosa acorensis is a wolf spider species occurring on all nine islands of the Azorean archipelago (Azores, Portugal) (Borges et al. 2010). It has a large Extent of Occurrence (EOO = 43,265 km²) and a relatively large Area of Occupancy (AOO = 636-2,228 km²). This species is the most widespread Azorean endemic spider and is particularly abundant from mid to high elevations in bogs, semi-natural pastures and a rare habitat at high elevations, the natural grasslands. The species is also able to occur in intensively managed pastures for dairy cattle. Based upon the large Extent of Occurrence, the good adaptation to human modified habitats, and few threats the species is assessed as Least Concern (LC).